Pengaruh Model Children Learning In Science (CLIS) terhadap Hasil Belajar IPA Siswa Kelas III UPT SPF SD Inpres Sambung Jawa 1 Kota Makassar - Nurul Ihza; Irmawanty Irmawanty; Hilmi Hambali (Journal on Education, 2024)
The aim to be achieved in this research is to determine the influence of the Children Learning In Science (CLIS) model on the science learning outcomes of class III students at UPT SPF SD Inpres Sambung Jawa 1 Makassar City. This research is a type of Quasi Experimental research. With a Pretest-Posttest Control Group Design. This research variable consists of the independent variable, namely the Children Learning in Science (CLIS) model and the dependent variable, namely learning outcomes. The population in this study was all class III students at UPT SPF SD Inpres Sambung Jawa 1 totaling 56 students. Data collection techniques use tests, observation sheets and documentation. The research instrument uses tests and observation sheets. The results of research in the experimental class obtained an average posttest score of 86.22, while the average posttest score for the control class was 74.24. Meanwhile, the results of the hypothesis test show that the value of tcount > ttable or 4.178 > 2.00488, then H1 is accepted and H0 is rejected. From these results it can be concluded that there is an influence of the use of the Childrean Learning in Science (CLIS) model on the science learning outcomes of class III students at UPT SPF SD Inpres Sambung Jawa 1 Makassar City.